Transfer of Teacher Training Skills in Classroom - Thapa, Tara Bahadur (Academic Voices: A Multidisciplinary Journal, 2013)
Teacher training helps to increase teaching and learning process in the classroom. Its impact in classroom situation brings a good result in all teaching learning process and children’s overall development. However, in spite of the intensive teacher training, the public school’s achievements seem poor day by day in the context of Nepal. Many factors play the role to transfer the training skills to the classroom successfully. The effect of training in teaching and learning denotes the betterment of overall situation of classroom activities. So this article highlights on the existing situation of teacher training and the transfer of its skills in the classroom. Academic Voices, Vol. 2, No. 1, 2012, Pages 69-73 DOI: http://dx.doi.org/10.3126/av.v2i1.8292